Investigating science investigation: a robust case study design. (2015) - Moeed, Azra
This paper presents a research design that resolves the personal tension between a scientific and educational approach to research. The purpose of the research was to investigate the phenomenon of science investigation (inquiry) and to explore the connectedness between motivation to learn, learning and assessment. Three discreet quantitative studies investigating; learning science investigation, motivation to learn science investigation, and assessment of science investigation were considered but rejected because the teacher and learner were considered to be central to this research and could not be separated. It was the desire to understand how the connectedness between the three elements played out for the teacher and the learner that led to a qualitative case study. The argument was that a robust research design, triangulation of theory and data, and an integrative approach to analysis, can provide insights that were otherwise unlikely.